Reputation vs selection effects in markets with informational asymmetries - Alysandratos, Theodore; Geōrganas, Sōtērēs; Sutter, Matthias (Discussion paper series, 2022)
In markets with asymmetric information between sellers and buyers, feedback mechanisms are important to increase market efficiency and reduce the informational disadvantage of buyers. Feedback mechanisms might work because of self-selection of more trustworthy sellers into markets with such mechanisms or because of reputational concerns of sellers. In our field experiment, we can disentangle self-selection from reputation effects. Based on 476 taxi rides with four different types of taxis, we can show strong reputation effects on the prices and service quality of drivers, while there is practically no evidence of a self-selection effect. We discuss policy implications of our findings.
Keywords: Graue Literatur